Fatty liver disease in dairy cattle – risk factors, symptoms and prevention - Elżbieta Bombik (Polish Society of Animal Production, 2020)
Fat cow syndrome (fatty liver disease) is a common metabolic problem in dairy cow production during the transition period, from the dry period to lactation. This syndrome occurs when due to liver uptake of non-esterified fatty acids (NEFAs), they are stored in excess as triacylglycerols (TAGs) in the liver. Currently, diagnosis of this disorder must be confirmed by a liver biopsy to determine the fat content of liver cells, as well as blood tests for increased levels of liver enzymes (GGT, SDH, AST, and bilirubin). Fat cow syndrome is associated with the occurrence of clinical diseases, decreased immunity, and problems with reproduction. It is a major problem in the herd health due to the high cost of veterinary services, a longer calving interval, and reduced longevity of cows, causing enormous economic losses. The best means of prevention is good nutrition and routine blood tests in the herd.